Inclination towards entrepreneurship among community college students in Malaysia - Ooi, Yeng Keat; Ahmad, Syuhymee; Hoe, Chee Hee; Hashim, Norashidah (Universiti Utara Malaysia, 2014)
Entrepreneurship has been acknowledged as a major growth engine and catalyst in driving a nation’s economic growth, innovation, competitiveness, wealth creation and these in turn generates new job opportunities.Along the same argument, Malaysia is also keen to encourage youths especially among the university graduates to be self-employed by becoming entrepreneurs. Unemployment among new university graduates is becoming a major problem in Malaysia and hence, the Malaysian government would like to see graduates becoming self-employed as entrepreneurs. In this respect, entrepreneurship has been identified as the possible panacea to cure current graduate unemployment.This study investigates the effect of entrepreneurship education on the role of Malaysian community college students’ inclination towards entrepreneurship.The main objectives of this study are: - i) determine whether the role of community college in promoting entrepreneurship significantly affects community college students’ inclination towards entrepreneurship; ii) to examine the effect of entrepreneurial curriculum and content on community college students’ inclination towards entrepreneurship; and iii) to examine whether the role models significantly affects community college students’ inclination towards entrepreneurship.The results of the study showed that 50.8 per cent of the community college students would consider starting a business as their future career whilst 32.8 per cent stated that they are likely to start a business after graduation.In terms of role models, parents, career counsellors and teachers/educators appear to have significant influence in community college students’ decision to pursue an entrepreneurial career.Hence, this study showed that community colleges play a vital role in fostering and promoting entrepreneurship in order to produce more entrepreneurial-inclined graduates.